The Effect on Foreign Direct Investment of Membership in the European Union - Randolph Luca Bruno; Nauro F. Campos; Saul Estrin (Institute of Labor Economics (IZA), 2020)
This paper explores the impact of EU membership on foreign direct investment (FDI). It analyses empirically how the effects of such deep integration differ from other forms and investigates what drives these effects. Using a structural gravity framework on annual bilateral FDI data for almost every country in the world, over 1985-2018, we find EU membership leads FDI into the host economy to be about 60% higher for investment from outside the EU, and around 50% higher for intra-EU FDI. Moreover, we find that the effect of EU membership on FDI is larger than from membership of NAFTA, EFTA, or MERCOSUR, and that the Single Market is the cornerstone of this differential impact.
Keywords: F21; F36; O52; 330; European Union; foreign direct investment; economic integration; Structural Gravity Model; single market